Demanding Epistemic Justice: Indigenous Youth as Indigenous Science Diplomats for a Sustainable Future - Gordon, Heather Sauyaq Jean (KULA, 2025)
This commentary begins with the author's background, which leads into explaining Indigenous Ways of Knowing, Knowledges, and Sciences. It examines the significance of Indigenous kinship perspectives offering a sustainable way to live, inherent in many Indigenous cultures. It then explores colonial epistemicide, evolving knowledge pluralism, and how to co-produce knowledge needed for evidence-based decision-making. It concludes with a discussion of the transformative role of Indigenous youth in demanding epistemic justice by serving as Indigenous Science Diplomats, promoting knowledge pluralism in evidence-based policy. These young leaders bridge ways of knowing and span power structures and cultural, epistemological, and disciplinary divides, fostering a more inclusive sustainability in the face of climate change. The commentary underscores the importance of empowering Indigenous youth as key actors in creating a sustainable future and advocates for greater recognition and integration of Indigenous Knowledges and Sciences in policy and practice, promoting a path toward epistemic justice and a sustainable planet.